2018
DOI: 10.1128/jvi.01541-17
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Fold Axis of the HIV-1 Capsid Lattice Is the Species-Specific Binding Interface for TRIM5α

Abstract: Rhesus TRIM5α (rhTRIM5α) potently restricts replication of human immunodeficiency virus type 1 (HIV-1). Restriction is mediated through direct binding of the C-terminal B30.2 domain of TRIM5α to the assembled HIV-1 capsid core. This host-pathogen interaction involves multiple capsid molecules within the hexagonal HIV-1 capsid lattice. However, the molecular details of this interaction and the precise site at which the B30.2 domain binds remain largely unknown. The human orthologue of TRIM5α (hsTRIM5α) fails to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…TRIM5α binding also affects residues in critical assembly interfaces, including the NTD-NTD and NTD-CTD intrahexameric interfaces and the CTD-CTD interhexameric dimer interface, in accordance with the observation that TRIM5α does not bind appreciably to CA monomers (51). Indeed, the mechanisms of capsid recognition by TRIM5α involve higher-order capsid assembly (48,26). While emerging evidence suggests that dynamics may play a role in capsid function (2,(15)(16)(17)(18), in-depth atomic-level investigations of the relevant timescales are needed to understand how dynamic allostery may fine-tune infectivity.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…TRIM5α binding also affects residues in critical assembly interfaces, including the NTD-NTD and NTD-CTD intrahexameric interfaces and the CTD-CTD interhexameric dimer interface, in accordance with the observation that TRIM5α does not bind appreciably to CA monomers (51). Indeed, the mechanisms of capsid recognition by TRIM5α involve higher-order capsid assembly (48,26). While emerging evidence suggests that dynamics may play a role in capsid function (2,(15)(16)(17)(18), in-depth atomic-level investigations of the relevant timescales are needed to understand how dynamic allostery may fine-tune infectivity.…”
Section: Discussionsupporting
confidence: 67%
“…The presence of the β-hairpin has been proposed to be an important feature in the assembly of the mature viral core (45,46) and may be exploited by TRIM5α as a molecular recognition motif (47), although this hypothesis is currently debated. A recent study suggested that the TRIM5α B30.2 domain recognizes the capsid through the capsid's trimeric interface, conferring species-specific HIV-1 restriction activity (48).…”
Section: Hexameric and Pentameric Subunits Have Distinct Dynamic Signmentioning
confidence: 99%
“…Attractive interactions between B-box domain residues were added to promote the formation of the crystallographically resolved trimer-of-dimer structures. Attractive interactions were added between SPRY and CA domain residues that demonstrated decreased or abolished TRIM5α binding in experimental mutagenesis studies 21,29 . (For a complete description on the models, see also Materials & Methods).…”
Section: Resultsmentioning
confidence: 99%
“…CypA has a much higher affinity for the CA protein (K D~1 0 μM) [38][39][40] , and the high-resolution crystallographic structure of CypA in complex with CA reveals that it binds to a flexible loop region that connects helices 4 and 5 (resid 80-100) 41 . Given the weak affinity between the SPRY and CA domains and the lack of available structural data, several studies have attempted to model the SPRY binding interface either using computational methods 42,43 or experimental mutagenesis 29,44 . Our CG simulations provide an alternative approach.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing viral load level has a strong association with decreasing survival probability [12]. and is associated with high-affinity binding and determines species-specific restriction of TRIM5α orthologues [19].…”
Section: Trim5α and Hiv-2mentioning
confidence: 99%